ANALYSIS SEARCH DATA USING THE NATIONAL INSTITUTE OF STANDARD AND TECHNOLOGY (NIST) METHOD ON CYBERCRIME - Turkhamun Adi Kurniawan; Arman Syah Putra; Nurul Aisyah (Journal of Innovation Research and Knowledge, 2022)
This research has a background on how to find data that has been lost or that has been deleted with an application that can help find the data, so this method will be able to find it. This method is the one used in this research. By using this method, it can be ascertained that the data will be determined using the NIST legal analysis scenario and legal export condition scenario methods so that it can be concluded that the search for data will be much easier and the search for data will find much greater. The problem raised in this research is how to find lost data or data that is sought in various systems. With this system, it can be ascertained that the data is analyzed as legal data and can be ascertained as evidence because the data was intentionally omitted or the data was intentionally hidden. The purpose of this study is how to find hidden or missing data. These data are important data that can be used as evidence in court as a legal basis for legal experts.